2021
DOI: 10.1016/j.trecan.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Better together: circulating tumor cell clustering in metastatic cancer

Abstract: Circulating tumor cells (CTCs) are vital components of liquid biopsies for diagnosis of residual cancer, monitoring of therapy response, and prognosis of recurrence. Scientific dogma focuses on metastasis mediated by single CTCs, but advancement of CTC detection technologies has elucidated multicellular CTC clusters, which are associated with unfavorable clinical outcomes and a 20-to 100-fold greater metastatic potential than single CTCs. While the mechanistic understanding of CTC cluster formation is still in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 88 publications
1
104
0
Order By: Relevance
“…CTCs, even obtained from a single patient at the same time, may show strong heterogeneity (see Section 3) and thereby varied metastatic potential. In addition, CTCs can exist in clusters (very strong metastatic factors) that can significantly influence cancer development [24].…”
Section: Influence Of Ctc Count On Chemotherapeutic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs, even obtained from a single patient at the same time, may show strong heterogeneity (see Section 3) and thereby varied metastatic potential. In addition, CTCs can exist in clusters (very strong metastatic factors) that can significantly influence cancer development [24].…”
Section: Influence Of Ctc Count On Chemotherapeutic Efficacymentioning
confidence: 99%
“…On the other hand, Illie et al found that CTC-positive patients with tobacco-induced chronic obstructive pulmonary disease may have developed lung cancer [23]. This suggests that cancer patients in the early stages of lung cancer could display high metastatic activity, such as higher CTC counts and formation of CTC clusters (a highly metastatic and aggressive form of CTC) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is notable that circulating tumour cell (CTC) clusters exhibit altered adhesion molecule profiles and ICAM-1 is one of the adhesion molecules that mediates aggregation of CTCs. The significance of multicellular CTC clusters for cancer patients was recently reviewed [177]. It should also be noted that the heterotypic CTC clusters include immune cells and CAFs and that their escape from the primary tumour site is enabled by leaky vasculature [177].…”
Section: Prospective Targets Of Adenosinergic Therapymentioning
confidence: 99%
“…The significance of multicellular CTC clusters for cancer patients was recently reviewed [177]. It should also be noted that the heterotypic CTC clusters include immune cells and CAFs and that their escape from the primary tumour site is enabled by leaky vasculature [177]. Finally, DNA methylation is an essential factor for stemness (re-)programming of CTCs [178].…”
Section: Prospective Targets Of Adenosinergic Therapymentioning
confidence: 99%
“…Furthermore, in patients with breast or prostate cancer, overexpression of the JUP gene that encodes plakoglobin has been associated with poor prognosis [ 4 ]. Other cell adhesion molecules, such as CD44 or ICAM1, have also been shown to be involved in the clustering of cancer cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%